Beyond Morality: Assessment of the Capacity of Faith-based Organizations (FBOS) in Responding to the HIV/AIDS Challenge in Southeastern Nigeria - Eze Edlyne ANUGWOM; Kenechukwu ANUGWOM (Tehran University of Medical Sciences, 2017)
Background: For the world can get rid of the HIV/AIDS pandemic by 2030, there is need for more to be done especially in the case of countries in Africa. In Nigeria, such efforts have included Faith-Based Organizations (FBOs) recognized as partners in the National Response Framework. However, the extent to which these FBOs contribute to efforts to control the pandemic will depend on their capacity. Therefore, this study aimed to ascertain the technical and managerial capacity of these FBOs to respond to the pandemic in Nigeria. Methods: We utilized social survey in examining the capacity of three purposively selected FBOs in the Southeast of Nigeria to respond to the pandemic. Thus, the focus group discussion and the key informant interviews were used. The data for the study was collected between Feb and Apr 2014. Results: The study discovered a general low capacity but high willingness of the FBOs to get involved. One of the FBOs studied was better placed than others and had even established committee on the pandemic. However, in another FBO, the pandemic was still seen largely with moral lens that blame those infected rather than provide support. All the FBOs were ambivalent on the use of condoms as a prevention method. Conclusion: There is need for sustained capacity building for the FBOs in order to provide them with knowledge on the pandemic and help them act out the role envisaged for them in the National Response Framework in Nigeria.